Paraloid B72 Versus Paraloid B72 with Nano-ZnO Additive as Consolidants for Wooden Artefacts - Tuduce Traistaru, Ana-Adriana; Timar, Maria Cristina; Campean, Mihaela; Croitoru, Catalin; Sandu, Ion (Materiale Plastice, 2012)
This article presents the study of the opportunities and limits of employing nano-ZnO as additive to Paraloid B72 solutions used for consolidation of degraded, frail wood. The experiments were carried out on degraded spruce samples (Picea abies) in different conservation levels that were extracted from a frail wooden element of a massive gateway from the historic centre of Brasov (Romania) during its restoration. In this respect the samples were dimensioned at (20x20x30) mm and divided into three batches according to their initial conservation state: level I, very degraded samples with obvious loss of resistance and cohesion; level II, samples highly degraded but with structural cohesion and level III, samples with little degradation. Two consolidant formulations based on Paraloid B72 were used: a solution of 10% in ethanol and acetone mixture 1/1 (coded C4) and a similar solution modified with nano-ZnO additive in proportion of 2.5 % (coded C4 -ZnO2.5). All the samples were treated by total immersion for 1 hour in the prepared consolidants. The application treatment efficiency was evaluated by determining the consolidant uptake Csp [Kg/m3] and retention WPG [%], while the actual effects of the consolidation procedure were evaluated by determining the compression strength parallel to the grain τc// [MPa] and the water absorption in a total immersion test, WA [%].
Keywords: wood consolidation; Paraloid B72; nano-ZnO; compressive strength; FTIR spectroscopy